A Practical Approach to Semicarbazone and Hydrazone Derivatives via Imino-isocyanates - Garland, Keira (Université d'Ottawa / University of Ottawa, 2014)
Isocyanates have a broad spectrum of uses and they are used in the production of many products including polyurethane polymers, coatings, adhesives, paints and foams. While isocyanates are widely studied and well represented in the literature, nitrogen substituted isocyanates are quite rare. Amino and imino-isocyanates are examples of nitrogen substituted isocyanates. Previous work within the group studied the reactivity of these intermediates in the alkene aminocarbonylation reaction, and used hydrazones and hydrazides as precursors of nitrogen substituted isocyanates. From there, a second reaction pathway was studied. This involved the reactivity of hydrazones with nucleophiles to develop a simple exchange reaction. In this work, the substitution reactivity involving imino-isocyanates will be presented. This will include the scope of nucleophiles and hydrazones as well as a discussion on the formation of the imino-isocyanates. This reactivity allows for the facile formation of a variety of hydrazones with the flexibility to start from common hydrazone precursors.
Keywords: imino-isocyanate; hydrazone; semicarbazone